Latino migrants’ healthcare use in the US and perceived immigration laws and consequences: A multivariable analysis - Carol L. Galletly; Timothy L. McAuliffe; Julia B. Dickson-Gomez; Laura R. Glasman; Dulce M. Ruelas (Travel Medicine and Infectious Disease, 2023)
Background: Using healthcare, whether for routine preventative examinations, chronic condition management, or emergent conditions, is an essential element of achieving and maintaining health. Over 44 million migrants live in the US today and nearly half (44.6 %) are Latino. To the extent that immigration law-related concerns deter US Latino migrants from using healthcare, they jeopardize the health of a substantial though marginalized US subpopulation. Methods: A multistate sample (N = 1750) of noncitizen adult, Spanish speaking Latino migrants (both undocumented and documented) living in the US completed a cross-sectional survey comprising a scale assessing perceptions of immigration laws and consequences related to healthcare use and whether they had received and/or needed but did not receive healthcare in the previous 12-months. Participants were recruited in community settings and by word-of-mouth. Univariate analyses examined associations among study outcomes and common predictors of healthcare use. Multivariable analyses examined the relative contribution of perceived immigration laws and consequences on healthcare use and unmet need. Results: Perceptions of immigration laws and immigration consequences were a significant predictor of not having received healthcare in the previous 12-months and having needed and not received healthcare in the same period, even when considered relative to common predictors of healthcare use. Immigration documentation status and preferred language predicted healthcare use in univariate analyses but not in the multivariable model. Conclusions: Perceived immigration laws and consequences related to healthcare use may influence migrants’ healthcare use. Effective interventions should be developed to address immigration-related concerns.